Prophylactic efficacy of 400 vs. 200 mg/kg /day calcium gluconate to prevent neonatal hypocalcemia - Apsera, Liza; Sianturi, Pertin; Nafianti, Selvi (Indonesian Pediatric Society, 2023)
Background Serum calcium is at its lowest level within 24–48 hours after birth, rendering the neonate vulnerable to hypocalcemia. In our center, despite prophylactic administration of 200 mg/kg/day calcium gluconate, the prevalence of neonatal hypocalcemia remains high. Aim To determine the prophylactic efficacy of 400 vs. 200 mg/kg/day calcium gluconate in preventing neonatal hypocalcemia. Methods A randomized clinical trial with a pre- and post-test experimental design was done on neonates who fasted or received only minimal enteral feeding. Subjects were randomized to receive either 400 mg/kg/day (intervention group) or 200 mg/kg/day (control group) of intravenous calcium gluconate. We compared serum ionized calcium levels on the first day of admission before calcium gluconate administration and on the third day of hospitalization between the intervention and control groups. Results The median ionized calcium levels in the intervention vs. control group before calcium gluconate administration was 1.16 (range 0.4-2.4) mmol/L vs. 1.15 (range 0.6-4.5) mmol/L , respectively (P=0.561). After three days of calcium gluconate administration, the median ionized calcium level was 1.19 (range 0.7-1.45) mmol/L vs. 1.19 (range 0.68-4.6) mmol/L in the intervention vs. control group, respectively (P=0.828). The difference in pre- vs. post-administration ionized calcium levels was significant within the intervention group (P=0.032), but not within the control group (P=0.128). Conclusion Prophylactic intravenous calcium gluconate at 400 mg/kg/day was not more effective in preventing neonatal hypocalcemia than 200 mg/kg/day.